2019
DOI: 10.7759/cureus.5061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Knowledge of Endotracheal Cuff Pressure Monitoring Among Critical Care Providers by Palpation of Pilot Balloon and By Endotracheal Tube Cuff Manometer

Abstract: Introduction Mishandled endotracheal cuff pressure may either make ventilation difficult or cause damage to the airway. Therefore, the aim of this audit was to assess the knowledge about endotracheal cuff pressure monitoring with a manometer and manual palpation of pilot balloon among critical care providers. Methods This audit includes 150 critical care providers having experience of handling endotracheal tube (ETT) cuff at critical care area of National Institute of Cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Strategies in the form of educational programmes should be implemented to enhance the nurses’ knowledge. This is especially important as previous studies conducted on nurses’ knowledge regarding ETT cuff pressure revealed differences in ICU nurses’ knowledge, leading to varying practices (Abubaker et al 2019 ; Jordan 2011 ; Jordan, Van Rooyen & Venter 2012 ; Mohammed et al 2016 ; Mwakanyanga, Masika & Tarimo 2018 ). A study by Mohammed et al ( 2016 ) showed that an educational programme including discussion groups and formal lectures accompanied by suitable teaching aids, such as handouts, posters, coloured pictures and a programme booklet, improved the knowledge of the nurses regarding ETT cuff pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies in the form of educational programmes should be implemented to enhance the nurses’ knowledge. This is especially important as previous studies conducted on nurses’ knowledge regarding ETT cuff pressure revealed differences in ICU nurses’ knowledge, leading to varying practices (Abubaker et al 2019 ; Jordan 2011 ; Jordan, Van Rooyen & Venter 2012 ; Mohammed et al 2016 ; Mwakanyanga, Masika & Tarimo 2018 ). A study by Mohammed et al ( 2016 ) showed that an educational programme including discussion groups and formal lectures accompanied by suitable teaching aids, such as handouts, posters, coloured pictures and a programme booklet, improved the knowledge of the nurses regarding ETT cuff pressure.…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations are also part of the preventive measures emphasized in the VAP prevention guidelines 10,11 . Despite the existence of such guidelines, evidence shows that variation in cuff maintenance practices and compliance with such guidelines are still suboptimal in some of the ICUs in developed countries like the United States, 6 Australia, and New Zealand 12,13 and in developing countries like Pakistan, 14 Sri Lanka, 5,15 and South Africa 16 …”
Section: Introductionmentioning
confidence: 99%
“…Variations in practice were noted in the frequency of monitoring, 14,17 technique of cuff pressure measurements, 5,12,18 and documentation 16 . Diversity in the frequency of monitoring endotracheal cuff pressure among nurses and ICUs was reported in international literature, with some monitoring every 2 to 4 hours; some every 6 to 12 hours; and others only if the need arose, such as when air leakage was noted 12,17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations